A study the availability of potassium in Samno area and the effect of that on growth of barley - Abdalla M. Alaswd (Journal of Pure & Applied Sciences, 2019)
This field experiment was carried out in Samno area which located between longitudes 14.43 and 14.75 degrees east and 27.17, 27.31 North. The aim of this study was to study the adequacy of available potassium in the soil to add the requirement of barley plant (Ampola category) and the effects of that on some characteristics of barley growth. during the growth season 2015-2016, two types of potassium fertilizers were used: potassium chloride (KCl), potassium sulphate (K2SO4) , The fertilizers were added at five levels (0, 25, 50, 75, 100) kg potassium / ha The results of this study showed that no significant differences in all studied parameters (total weight of plant, straw weight, grain weight, weight of 1000 grain) when the added potassium (25, 50, 75, 100) kg / ha were compared with the control. As for the effect of both fertilizers( potassium chloride and potassium sulphate) on the growth indicators studied, the results showed no difference between treatments. The study concluded that, this soil contains enough available  potassium for barley plant under study without the need to add potassium fertilizer to the soil.